Thermal Regeneration in Etched-Core Fiber Bragg Grating - Yang, H.Z.; Chong, W.Y.; Cheong, Y.K.; Lim, K.S.; Pua, C.H.; Harun, Sulaiman Wadi; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Thermal regeneration is observed in etched-core fiber Bragg gratings (FBGs) with a fiber diameter of 5.6 μm. Etched-core FBGs are prepared by chemical etching using a hydrofluoric acid solution. Annealing is applied for all gratings to induce thermal regeneration. Thermal regeneration of FBG is observed at 680°C. The temperature sensitivity of regenerated etched-core FBGs is measured to be 13.9 pm/°C for a temperature range between 25°C and 700°C. With its high temperature resistance and large evanescent field interaction with its surrounding, thermally regenerated etched-core FBG has potential applications in high temperature sensing.